A revision of the genus Solter Navás, 1912 for Maghreb and West Africa with descriptions of five new species (Neuroptera, Myrmeleontidae) - Michel, Bruno (Zootaxa, 2014)
The Solter species of the Maghrebian and sub-Saharan West African Regions are revised. Nine species are recorded, S. bouyeri nov. sp., S. dogon nov. sp., S. francoisi nov. sp., S. leopardalis nov. sp., S. liber Navás, S. lucretii nov. sp., S. naevipennis Navás, S. neglectus Navás stat. rev. and S. rothschildi Navás. A lectotype is designated for the last species. A tenth species, S. ardens (Navás), is classified as incertae sedis. Solter virgilii Navás is removed from the species present in the area covered by this study. The larva of S. leopardalis is described. All species are illustrated including habitus, morphological characters and male genitalia. An identification key is provided.